Multicomponent Adsorption of Butane, NO and SO on Activated Carbon - Falk Ahnert; Wolfgang Heschel (Adsorption Science & Technology)
Dynamic adsorption experiments have been carried out with the help of an FT-IR (Fourier-Transform InfraRed) spectrometer. Fixed bed adsorption breakthrough curves were obtained for n-butane, SO 2 and NO 2 gases as well as for the reaction products NO, N 2 O and CO 2 . The adsorption of SO 2 and NO 2 on activated carbon was studied both during single- and co-adsorption experiments at 30°C. The activated carbon used exhibited a disadvantage towards NO 2 adsorption in that it was partly converted to NO and immediately desorbed as NO. A further reaction to N 2 O could also be observed. The activated carbon was rapidly altered and lost a notable part of its loading capacity as a result of the presence of water and oxygen. During co-adsorption, SO 2 reacted with NO 2 (both as adsorbed species) and produced an additional amount of NO. An ash-tree spherical activated carbon with an extended surface area (1000 m 2 /g) was used in all experiments.